PENGARUH VARIASI WAKTU SENTRIFUGASI NILAI HEMATOKRIT MENGGUNAKAN METODE MIKROHEMATOKRIT DI UNIVERSITAS BINAWAN - Nurcholis Majid (Jurnal SainHealth, 2023)
Hematocrit is the total volume of red blood cells in 100 ml of blood expressed as a percentage of blood volume. Hematocrit examination is needed to help diagnose diseases such as anemia and dengue hemorrhagic fever (DHF) to determine the total volume of red blood cells or erythrocytes. The normal value for hematocrit examination is 40-54% for males and 37-47% for females. The purpose of this study was to determine the effect of variations in centrifugation time on hematocrit values using the microhematocrit method. This type of research is quantitative using experimental method with cross sectional design. The method used for hematocrit examination is the microhematocrit method with variations in centrifugation time of 2 minutes, 3 minutes, 4 minutes, and 5 minutes as a control with a speed of 12,000 rpm. The respondents of this study were 35 respondents and the samples of this study were 35 venous blood samples taken from Binawan University students, Medical Laboratory Technology Study Program batch 2021 and 2022. The average result of the 2-minute centrifugation hematocrit value examination is 37.87%, 3-minute centrifugation is 37.57%, 4-minute centrifugation is 37.30%, and 5-minute centrifugation is 37.25%. The Wilcoxon test results show the Sig. (2-tailed) of 2-minute centrifugation compared with 5 minutes is 0.00 (<0.05), 3-minute centrifugation compared with 5 minutes is 0.001 (<0.05), 4-minute centrifugation compared with 5 minutes is 0.560 (>0.05). The results of this study showed that hematocrit values with centrifugation times of 2 minutes and 3 minutes compared to 5 minutes had significant differences in hematocrit values.